1996
DOI: 10.1159/000264290
|View full text |Cite
|
Sign up to set email alerts
|

Anti-TJa Alloimmunization (anti-PP1Pk)

Abstract: Anti-TJa alloimmunization is an extremely rare condition which can cause miscarriages during the first and second terms of pregnancy. At 20-year-old female patient, an anti-TJa carrier, was given plasma transfusions in the course of her first two pregnancies. The cordocentesis, which was the main follow-up test during the first pregnancy, could not be carried out during the second pregnancy due to the presence of a huge subchorionic hematoma. Both pregnancies were characterized by fetal growth retardation, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Plasmapheresis can reduce the anti-PP1Pk antibody titer to prevent miscarriage. Trophoblast cells can express antigens in the rst trimester, so plasmapheresis should be started at 5-7 weeks gestation to reduce the antibody titer to between 1:16 and 1:32 [22]. Plasmapheresis is usually performed using a centrifugal plasma separator for simple plasmapheresis, while some studies have found that double-ltration plasmapheresis is safer for pregnant women [26].…”
Section: Discussionmentioning
confidence: 99%
“…Plasmapheresis can reduce the anti-PP1Pk antibody titer to prevent miscarriage. Trophoblast cells can express antigens in the rst trimester, so plasmapheresis should be started at 5-7 weeks gestation to reduce the antibody titer to between 1:16 and 1:32 [22]. Plasmapheresis is usually performed using a centrifugal plasma separator for simple plasmapheresis, while some studies have found that double-ltration plasmapheresis is safer for pregnant women [26].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the successful therapeutic use of plasmapheresis in removing cytotoxic anti‐P from maternal plasma (Yoshida et al, ; Rock et al, ). However, this line of treatment is most successful if started as early as possible in the first trimester, when P antigens first appear on the trophoblastic tissue, and is continued throughout the second trimester (Haentjens‐Verbeke et al, ). Plasmapheresis has to be undergone several times a week, making it hard to manage in remote areas.…”
Section: Discussionmentioning
confidence: 99%